1991
DOI: 10.1097/00004872-199103000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits in the trial of the European Working Party on High Blood Pressure in the Elderly

Abstract: Hypertensive patients over the age of 60 years were admitted to a double-blind placebo-controlled trial. Patients in the actively treated group received a combined potassium-losing and -sparing diuretic (triamterene 50 mg plus hydrochlorothiazide 25 mg; n = 416); this dose could be doubled and methyldopa (up to 2g, daily) was added in 35% of patients when blood pressure remained high. The placebo group (n = 424) received matching capsules and tablets. Adverse effects were assessed in the double-blind period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 1 publication
0
51
0
2
Order By: Relevance
“…A number of other reasons may account for the reluctance of doctors to treat elderly patients with hypertension such as concerns about poor compliance, side-effects and adverse effects of lowering blood pressure excessively [16][17]. These issues remain unexplored with respect to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other reasons may account for the reluctance of doctors to treat elderly patients with hypertension such as concerns about poor compliance, side-effects and adverse effects of lowering blood pressure excessively [16][17]. These issues remain unexplored with respect to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that diuretic usage did not slow but rather accelerates renal progression in hypertensive patients despite reducing blood pressure. For example, the EWPHE [19], SHEP [20], INSIGHT [21], and ALLHAT [17] studies all reported that the usage of diuretics was statistically associated with a greater decline in renal function compared with the other treatment groups. Thus, while diuretics reduce blood pressure and blood pressureassociated events such as stroke and heart failure, they may be less effective at slowing renal disease or reducing cardiovascular events.…”
Section: Clinical Evidence For Hyperuricemia In Renal Diseasementioning
confidence: 99%
“…Even though there is an abundance of evidence supporting the beneficial effects of thiazide diuretics on cardiovascular outcomes, these agents may accelerate the onset of T2DM in patients with hypertension (particularly when used in high doses) [77,[87][88][89][90][91][92][93], although older studies often had method limitations [93]. In the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attacks Trial (ALLHAT) [70], the odds ratio of developing of developing T2DM at 2 years was significantly lower for lisinopril and amlodipine (0.55, P < .…”
Section: Thiazide Diuretics Clinical Datamentioning
confidence: 99%
“…Thiazide diuretics worsen glycemic control in a dose-dependent fashion by decreasing insulin secretion and peripheral insulin sensitivity [77,[87][88][89]97]. Hypokalemia (and perhaps hypomagnesemia) may play an important role in thiazide-induced glucose intolerance [77,[97][98][99], and deterioration in glucose metabolism occurs even with minimal decreases in serum potassium levels [90].…”
Section: Mechanismsmentioning
confidence: 99%